Topological Completeness for Higher-Order Logic - Awodey, Steve; Butz, Carsten (BRICS Report Series, 1997)
Using recent results in topos theory, two systems of higher-order logic are shown to be complete with respect to sheaf models over topological spaces - so-called "topological semantics". The first is classical higher order logic, with relational quantification of finitely high type; the second system is a predicative fragment thereof with quantification over functions between types, but not over arbitrary relations. The second theorem applies to intuitionistic as well as classical logic.